Role of radiotherapy to bulky disease in elderly patients with aggressive B-cell lymphoma. - Held, G.; Murawski, N.; Ziepert, M.; Fleckenstein, J.; Poschel, V.; Zwick, C.; Bittenbring, J.; Hanel, M.; Wilhelm, S.; Schubert, J.; Schmitz, N.; Loffler, M.; et al. (J Clin Oncol, 2014)
PURPOSE: R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) is standard care for aggressive B-cell lymphoma. A prospective trial was conducted to investigate the role of additive radiotherapy (RT) to bulky and extralymphatic disease. PATIENTS AND METHODS: The best arm of the RICOVER-60 trial (6xR-CHOP-14+2R [R-CHOP administered once every 2 weeks plus two additional applications of rituximab] plus involved-field RT [36 Gy] to sites of initial bulky [>/= 7.5 cm] disease and extralymphatic involvement) was compared with a cohort receiving the same immunochemotherapy but without RT in an amendment to the RICOVER-60 trial (RICOVER-noRTh) in a prospective fashion. RESULTS: After a median observation time of 39 months, 164 of 166 RICOVER-noRTh patients were evaluable. In a multivariable analysis of the intention-to-treat population adjusting for International Prognostic Index risk factors and age (> 70 years), event-free survival (EFS) of patients with bulky disease was inferior without additive RT (hazard ratio [HR], 2.1; 95% CI, 1.3 to 3.5; P = .005), with trends for inferior progression-free (PFS; HR, 1.8; 95% CI, 1.0 to 3.3; P = .058) and overall survival (OS; HR, 1.6; 95% CI, 0.9 to 3.1; P = .127). In a per-protocol analysis with 11 patients in RICOVER-noRTh excluded for receiving unplanned RT, multivariable analysis revealed HRs of 2.7 (95% CI, 1.3 to 5.9; P = .011) for EFS, 4.4 (95% CI, 1.8 to 10.6; P = .001) for PFS, and 4.3 (95% CI, 1.7 to 11.1; P = .002) for OS for patients not receiving RT to bulky disease. CONCLUSION: Additive RT to bulky sites abrogates bulky disease as a risk factor and improves outcome of elderly patients with aggressive B-cell lymphoma. Whether RT can be spared in patients with (metabolic) complete remission after immunochemotherapy must be addressed in appropriately designed prospective trials.
Keywords: Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/therapeutic use; Antineoplastic Combined Chemotherapy Protocols/therapeutic use; Combined Modality Therapy; Cyclophosphamide/therapeutic use; Doxorubicin/therapeutic use; Female; Humans; Lymphoma, B-Cell/drug therapy/pathology/*radiotherapy; Male; Middle Aged; Prednisone/therapeutic use; Prognosis; Prospective Studies; Risk Factors; Rituximab; Treatment Outcome; Vincristine/therapeutic use